357. Complications and Outcomes of Obese Patients Hospitalized with COVID-19. (31st December 2020) - Shallal, Anita; Morrison, Austin R; Brar, Indira; Suleyman, Geehan
Abstract: Background: Coronavirus disease 2019 (COVID-19) has greatly affected the US, where obesity is present in over 40% of the population. Evidence suggests that obesity is associated with a higher risk of developing severe disease and complications. The objective of this study was to assess the relationship between body mass index (BMI) and outcomes in hospitalized patients with COVID-19. Methods: A retrospective cohort study of patients with confirmed COVID-19 infection at Henry Ford Health System in metropolitan Detroit from March-May 2020. Demographics, comorbidities, severity of illness, complications, treatment and outcomes of obese (BMI > 30) and non-obese (BMI < 30) patients were compared. Data were analyzed using SPSS. Results: Summary of results comparing non-obese and obese patients is presented in tables 1 and 2. Median BMI (kg/m 2 ) in each group was 26 and 36.5, respectively. Age and black race differed significantly between the two groups (p< 0.001). Younger patients were more obese compared to older patients. Diabetes and obstructive sleep apnea (OSA) were significantly more common in obese patients. Obese patients were significantly more likely to receive antibiotics in the ED (p=0.015), require vasopressors for shock (p=0.004), and undergo renal replacement therapy (p=0.005). Although 37% of obese patients were intubated, obesity was not a significant risk factor for mechanical ventilation (MV). 30-day readmission and mortality were significantly higher in non-obese patients. In the regression analysis, age over 60, tachypnea at admission, acute kidney injury, and diabetes were significantly associated with need for MV, but not BMI. Conclusion: In our cohort, a high frequency of obesity is noted among black and younger patients. Obese patients were more likely to require intensive treatments, including renal replacement therapy and vasopressors but not mechanical ventilation. Complications and outcomes in COVID-19 should be further evaluated by BMI categories. Disclosures: Indira Brar, MD, Gilead (Speaker's Bureau)janssen (Speaker's Bureau)ViiV (Speaker's Bureau)